Towards Standardizing Medicolegal Practices In India: Challenges and Solutions (Journal of Forensic Medicine & Toxicology, 2025)
In India, Medicolegal cases require meticulous examination and evidence collection to support legal investigations, yet the absence of a standardized national medicolegal code leads to inconsistent practices. Currently, only a few states and institutions have developed their own codes, leaving many healthcare facilities, particularly in resource-limited settings, reliant on outdated or ad-hoc protocols. This variability complicates workflows, especially for junior consultants, medical graduates working in district hospitals performing medicolegal duties and foreign-trained medical graduates unfamiliar with Indian procedures, risking suboptimal evidence collection and documentation. A national medicolegal code is pro posed to standardize protocols for examination, sample preservation, and stakeholder responsibilities, ensuring unifor mity and clarity. Such a code would align with updated criminal laws, address logistical challenges like evidence storage, and incorporate guidelines for diverse medicolegal scenarios, including sexual violence, autopsies, and disaster victim identification. Despite challenges in enforceability due to state jurisdiction over law and order, voluntary adoption by states, endorsed by the Union government, could streamline practices, ultimately improving medicolegal service quality and aiding the justice delivery system across India. This review article discusses several practical difficulties in medicole gal practice, challenges in creating a national medicolegal code, and proposes recommendations to move forward.
Keywords: Evidence, India, Medico-Legal Case, National Medicolegal Code and Manual (MLMC)